Design of a smart garment for fencing: measuring attractiveness using the AttrakDiff Mini method - Vieira, Daniel (2023)
In this study, a new hypothesis for the design of a smart fencing garment, developed through a user-centred design process, is presented and a pre-evaluation of the design by applying the AttrakDiff Mini method is proposed. With the Portuguese Fencing Federation’s support, a survey was shared with the 37 affiliated weapons rooms. It was possible to validate 36 participations, 54.1% men (n = 20) and 45.9% women (n = 16) residing in Portugal. The questionnaire consists of 4 scales, divided into 10 items that made it possible to assess the hypothesis’ usability, identity, stimulation, and attractiveness. It is statistically possible to quantify the relationship between the dependent variable (attractiveness) and the independent variables (pragmatic quality, hedonic quality-identity, hedonic quality-stimulation), such as the correlations between these variables. At the end of the analysis, it was possible to conclude that the participants evaluate the hypothesis positively, considering the envisioned fencing suit possible to use and attractive.